Student’s Reading Skills on The Lhokseumawe Coast: A Case Study at State Elementary School 15 Banda Sakti - Khalila, Faiza; Iqbal, Muhammad; Ahyar, Juni (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This research aims to analyze the problems of students’ reading skills on the coast of Lhokseumawe at Banda Sakti 15 State Elementary School. This research uses a qualitative approach with a case study method. The research sample was selected using purposive sampling involving 10 fifth grade students, 10 parents and 1 teacher. Data was collected through reading tests, interviews and analyzed through three stages, namely data reduction, data presentation and drawing conclusions. The main focus of the research is fluency, voice clarity, pronunciation and intonation. Time triangulation is used to test the validity of the data. This research was carried out on May 29 s.d. June 29 2024 in Ujong Blang Village, Banda Sakti District, Lhokseumawe City. The research results show that students’ reading skill levels vary greatly. As many as five out of ten students show significant difficulties in reading, caused by factors such as difficulty recognizing and combining letters into words, as well as reading word by word without comprehensive understanding. This reflects that most are still at the basic stage and have not yet reached reading proficiency. These findings emphasize the importance of collaboration between parents and schools to create an environment that supports the development of students' reading skills both at home and at school.